Step
*
2
2
of Lemma
extend-name-morph-rename-one
1. I : Cname List
2. K : Cname List
3. f : name-morph(I;K)
4. z : Cname
5. z1 : Cname
6. v : Cname
7. ¬(z1 ∈ I)
8. ¬(z ∈ I)
9. ¬(v ∈ K)
10. x : nameset([z / I])
11. ¬(x = z ∈ Cname)
⊢ (f x) = if isname(x) then if eq-cname(x;z1) then v else f x fi  else x fi  ∈ extd-nameset([v / K])
BY
{ ((RWO "isname-nameset" 0 THEN Auto) THEN Reduce 0) }
1
1. I : Cname List
2. K : Cname List
3. f : name-morph(I;K)
4. z : Cname
5. z1 : Cname
6. v : Cname
7. ¬(z1 ∈ I)
8. ¬(z ∈ I)
9. ¬(v ∈ K)
10. x : nameset([z / I])
11. ¬(x = z ∈ Cname)
⊢ (f x) = if eq-cname(x;z1) then v else f x fi  ∈ extd-nameset([v / K])
Latex:
Latex:
1.  I  :  Cname  List
2.  K  :  Cname  List
3.  f  :  name-morph(I;K)
4.  z  :  Cname
5.  z1  :  Cname
6.  v  :  Cname
7.  \mneg{}(z1  \mmember{}  I)
8.  \mneg{}(z  \mmember{}  I)
9.  \mneg{}(v  \mmember{}  K)
10.  x  :  nameset([z  /  I])
11.  \mneg{}(x  =  z)
\mvdash{}  (f  x)  =  if  isname(x)  then  if  eq-cname(x;z1)  then  v  else  f  x  fi    else  x  fi 
By
Latex:
((RWO  "isname-nameset"  0  THEN  Auto)  THEN  Reduce  0)
Home
Index